Synthesis, characterization, biological evaluation and docking of coumarin coupled thiazolidinedione derivatives and its bioisosteres as PPARγ agonists - Shukla S.; Kumar P.; Das N.; Moorthy N.S.H.N.; Shrivastava S.K.; Trivedi P.; Srivastava R.S. (My University, 2025)
Thiazolidinedione (TZD) derivatives are the novel class of oral antidiabetic drugs which are selective agonist for the nuclear PPAR γ that enhances the transcription of several insulin responsive genes but TZDs are known to cause weight gain, hepatotoxicity and fluid retention. So a new series of coumarin coupled thiazolidinedione derivatives and its bioisosters (oxazolidinedione and imidazolidinedione) were synthesized by Knoevenagel condensation of 4-((7-hydroxy-2-oxo-2H-chromen-4-yl) methoxy) benzaldehyde with 2,4 thiazolidinedione and its bioisosteres. The structures of these compounds were established by means of FT IR, 1H-NMR, elemental analysis and mass spectroscopy. All the compounds were screened for antidiabetic activity in streptozotocin induced diabetic wistar male rats. Most of the compounds revealed significant antidiabetic activity when compared with the standard drug rosiglitazone. Compounds 5 & 6 containing oxazolidinedione ring system were found to be more active than compounds having thiazolidinedione and imidazolidinedione nucleus. Molecular docking was performed on 2 PRG protein by using the software Glide (Schrödinger, LLC, USA). The QikProp program was used to obtain the pharmacokinetic properties of analogues. © 2012 Bentham Science Publishers.